Students’ beliefs towards written CF and their impact on writing accuracy in EFL class: A Pakistani EFL context - Mehmood Ul Hassan, Dr.Hisham Dzakiria (International Journal of Advanced Science and Technology, 2020)
The effectiveness of different types of written CF to improve EFL learners’ writing accuracy has been an issue which has currently received a lot of attention in EFL field. The current study is the continuation of that focus by probing whether beliefs about written CF are varied between the university students of two different contexts. Whether differences of beliefs between two groups have impact on students’ uptake and retention. The study also investigated whether there are differences in the types of written CF that is the most useful and effective in two different contexts. By comparing students’ contexts and investigating beliefs about written CF, this study investigated the topic from cognitive perspective which is in contrast to the previous studies on cognitive perspective. Quantitative approach was used to collect data through five point Likert Scale questionnaire and writing prompts. Regarding writing prompts, the study used a pre-test, post-test, and delayed post-test, second delayed post-test design where written CF was given after the pre-test and the initial post-test. The students were placed in two groups according to their preferred written CF: direct CF group, indirect CF group and third was control group, hence; given no written CF.